Burden of common mental disorders in a community health centre sample - Ahmad, Farah (Can Fam Physician, 2016)
OBJECTIVE: To examine the rates of common mental disorders (CMDs) such as depression, anxiety, posttraumatic stress disorder (PTSD), and alcohol use in an urban community health care centre (CHC) serving vulnerable immigrant and ethnoracial communities in order to improve knowledge on the rates of CMDs specific to these groups accessing primary care settings. DESIGN: English or Spanish, self-administered, tablet-based survey known as the Interactive Computer-Assisted Client Assessment Survey (iCCAS). SETTING: Access Alliance Multicultural Health and Community Services CHC in Toronto, Ont. PARTICIPANTS: Adult patients waiting to see a clinician. MAIN OUTCOME MEASURES: The iCCAS screened for depression (using the PHQ-9 [Patient Health Questionnaire]), anxiety (using the GAD-7 [Generalized Anxiety Disorder 7-item scale]), PTSD (using the PC-PTSD [Primary Care PTSD Screen]), and alcohol dependency (using the CAGE questionnaire); those with an existing diagnosis and active treatment for one of these conditions were not asked to complete that condition-specific screening scale. An exit survey measured demographic characteristics and relevant indicators. RESULTS: A response rate of 78.6% was achieved. The iCCAS survey was completed by 75 patients (26 men and 49 women) with a mean age of 36.5 years. Almost all were first-generation immigrants: 32.0% originated from Latin America, 28.0% from South Asia, and 17.3% from Africa or the Middle East. Major depression was found among 44.0% of participants (11 with diagnosis and treatment, 22 with a score of 10 or greater on the PHQ-9). Generalized anxiety disorder was present in 26.7% of participants (7 with diagnosis and treatment, 13 with a score of 10 or greater on the GAD-7 scale). Posttraumatic stress disorder was detected in 37.3% of participants (7 with diagnosis and treatment, 21 with a score of 3 or greater on the PC-PTSD tool). Alcohol dependency was found among 10.7% of participants (1 with diagnosis and treatment, 7 with a score of 2 or greater on the CAGE questionnaire). CONCLUSION: The high rates of probable depression, generalized anxiety, and PTSD that were found in the studied population suggest a need for systematic assessment of CMDs in CHCs, as well as training and resources to increase readiness to handle identified cases.